Oligodon saiyok, a new limestone-dwelling kukri snake (Serpentes: Colubridae) from Kanchanaburi Province, western Thailand - Sumontha, Montri; Kunya, Kirati; Dangsri, Siriwat; Pauwels, Olivier S. G. (Zootaxa, 2017)
We describe Oligodon saiyok sp. nov. from Benjarat Nakhon Cave Temple, Sai Yok District, Kanchanaburi Province, western Thailand. It is characterized by a maximal known SVL of 626.1 mm; 13 maxillary teeth, the posterior two enlarged; 8 supralabials; 17-17-15 dorsal scale rows; 181–187 ventrals and 38–43 subcaudals; a single anal; hemipenes extending in situ to the 18th subcaudal; dorsum with 21–22 dark blotches or white rings without vertebral or lateral stripes; and venter with a dense network of subrectangular dark blotches. It is the 7th squamate species believed to be endemic to Sai Yok District.